The intensity of private funding and the results of university? Firm interactions: the case of Brazil - Márcia Siqueira Rapini; Tulio Chiarini; Pablo Bittencourt; Thiago Caliari (Innovation & Management Review, 2019)
Purpose - The purpose of this paper is to investigate the academic side of university - firm linkages, reporting the results of research (called the " BR Survey " , a primary database) conducted in Brazil with leaders of research groups that interacted with firms. The authors analys ed the answers from 662 research groups (from both universities and research institutes) to investigate whether the intensity of private funds affects the results of the interactions . The main intent is to answer the following question: Is there a difference between funding sources and the type of results achieved by research groups when interacting with firms? Design/methodology/approach - To verify the impact of some variables on the perception of the main results of university - firm interactions, highlighting the impact of funding sources, the authors present a Logit Model defined with binary dependent variables. The null value is categorized as a "scientific result" (new scientific discoveries and research projects; publications, theses and dissertations; human resources "and students" education) and the value 1 is classified as an " innovative/technological result " (new products, artefacts and processes; improvement of industrial products and processes; patents, software, design and spin-off firms). Findings - The authors found that the modes of interaction (relationship types) and some knowledge transfer channels, besides the number of interactions with firms, have statistically significant coefficients, so their values present different impacts on the results of the interaction. The results suggest that the Brazilian innovation policy towards a more active and entrepreneurial role of universities is fostering innovative/ technological results from university - firm interactions. Originality/value - The originality of the study lies on the results found that given the fact that private funding sources do not affect the conventional mission of Brazilian universities - teaching and research - university research groups should be even more incentivized to search for private funds to carry out their research. This may be a solution to the public fund scarcity and may help in reducing the historical distance between universities and firms in Brazil.
Keywords: 650; Brazil